Occupational upgrading, social inclusion and collective skill formation in the transition to the knowledge economy - Niccolo Durazzi; Simone Tonelli (European Trade Union Institute (ETUI), 2024)
Collective skill formation systems were central to sustaining a high-road approach to economic development in industrial societies while maintaining social inclusion. But can they still deliver in knowledge-based societies, both economically and socially? This article argues that nothing intrinsically prevents collective skill formation systems from adapting successfully to the knowledge economy. Such adaptation is not automatic, however. Rather, it depends on the willingness of key actors-unions, employers and the government-to actively adjust such systems to meet the needs of a labour market that has changed fundamentally, primarily because of technological change. Adaptation to the needs of the knowledge economy is thus likely to take country-specific forms and be politically mediated by power dynamics structuring actors' relationships. The argument is probed empirically through a panel analysis testing the effects of collective skill formation systems on a range of socio-economic outcomes and country case studies of Austria, Germany and Switzerland, which illustrate the political dynamics underpinning reforms of collective skill formation systems. Overall, the empirical evidence supports the argument, but it also points towards some difficulties that collective skill formation systems may face in maintaining social inclusion, hinting at the key role that unions may play in that respect.
Keywords: 330; Knowledge society; Investment in education; Social integration; Education policy; Germany; Austria; Switzerland; OECD countries; Wissensgesellschaft; Bildungsinvestition; Soziale Integration; Bildungspolitik; Deutschland; Österreich; Schweiz; OECD-Staaten